LANGUAGE CHARACTERISTICS OF BEAUTY PRODUCT ADVERTISEMENTS - Yenny Lestari Br. Sembiring; Berlin Sibarani; Lince Sihombing (LINGUISTIK TERAPAN, 2020)
The objectives of this study are to describe the linguistics characteristics of beauty product advertisements, to investigate the influence of buyer behaviors towards the beauty products advertisements. The data for the study were phrases, and sentences drawn from selected beauty products advertisemets. The linguistics characteristics of language are analysed based on Chaer theory and the influence of the consumer behaviors is based on Rapp and Collins theory. The results showed that (1) Based on the sentence,which is devided into(a) naturalness and unnatural (b) Number of sentence forming clauses (c) active and passive sentence. (2) based on phrase, which is divided into (a) basic phrase and derivative phrase, (b) phrase function,which divided into nominal phrase, verbal phrase, adjective phrase, and prepositional phrase.(3) Based on language functionm which divided into (a) evocative, informative, persuasive and powered language. Based on the result of study, it can be seen that the number of no advertisement factors presentations on on consumer buying behavior was 62,6 %, while the advertising language factors was only 37,4 %. This means that the language of beauty product advertising does not have a strong relationship with consumer buying behavior. The language is only able to trigger consumer to look for more detailed explanation and find more information from more trusted sources. Therefore, the language of advertising has a relationship that is not strong and indirect with buying behavior by consumers.  Keywords: Linguistic Characteristics, Consumer Behavior, Beauty Products, Advertisement.